'Leaders like children playing with a grenade?' : an analysis of how the Arab Spring was received in South Africa - Gevers, Tristan Ronald (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2013)
When the Arab Spring took place, it took the world by surprise and sparked renewed interest in the idea of revolution. With differing opinions on what caused such a revolutionary wave throughout the North African and Middle Eastern region, many began looking at their own countries, and South Africa was no different. A debate was sparked in South Africa, as to whether there would be a revolution or not. What I originally set out to accomplish is to find out which side of the debate would be correct through the philosophical context of revolutionary theory. Initially, we attempted to define and consider the history of revolutionary theory. We found that revolutionary theory has gone through four generation and that even finding a theoretically informed definition is difficult. Following this, we considered some social-psychological theories of revolution as well as theories of moral indignation. We found that these theories were incredibly informative and that they provide some insight into the reasoning for revolutionary fear in the South African debate. Through the use of opinion pieces, we then considered the South African debate, and "“ using socialpsychological theories and the theories of moral indignation - found that both sides of the argument had valuable points, however, they often lacked some foresight. With tentative agreement, we found that the side arguing that there would a revolution in South Africa had a more valuable argument, despite its limitations. However, far more research is required before one can "“ with more accuracy "“ predict a revolutionary occurrence in such a way as was done in South Africa.
Keywords: Arab Spring, 2010-; Revolutions; Arab countries -- Social conditions -- 21st century; South Africa -- Social condtions -- 21st century